IMMUNOSTIMULATION AS ADJUVANT FOR THE CHEMOTHERAPY OF EXPERIMENTAL SCHISTOSOMIASIS - Luciana M. SILVA; Zilton A. ANDRADE (Revista do Instituto de Medicina Tropical de São Paulo, 1997)
Immunosuppressed animals respond poorly to schistosomal chemotherapy and that a proper response can be restored by the administration of immune serum. Present study attempts to search whether immunological stimulation would increase drug effectiveness. Swiss mice infected with 50 S. mansoni cercariae were later treated with complete Freund's adjuvant. Treatment with oxaminiquine was made with 100 mg/kg.b.w., 25 mg/kg.b.w. and 50 mg/kg/b.w., the last two doses representing a fourth and a half of the recommended curative dose. Appropriate controls for the drug, the adjuvant and the infection were also studied. The serum-level of ant-S. mansoni antibodies (ELISA) and recovery of worms by perfusion of the portal vein system were the evaluated parameters. Statistical analysis of the results failed to reveal significant differences in worm recovery between adjuvant-stimulated animals treated with oxamniquine and any of the treated controls receiving the same amount of the drug. Although total lack of immunity interferes with curative treament the usual immune response seems to be sufficient to allow for curative drug action in schistosomiasis and thus apparently does not need to be artificially stimulated Animais imunodeprimidos respondem mal ao tratamento anti-esquistossomótico. A capacidade para responder adequadamente pode ser restaurada pela administração de soro imune. Não se sabe se a imunoestimulação de animais normais pode aumentar a eficácia da droga. Camundongos infectados com 50 cercárias do Schistosoma mansoni e tratados 2 meses depois com adjuvante de Freund responderam da mesma forma que os controles não imunestimulados ao tratamento com 25, 50 e 100 mg/kg pc de oxamniquine. Não houve correlação, entre níveis de anticorpos séricos e a eficácia da droga. Concluiu-se que embora a imunodepressão afete a eficácia da quimioterapia anti-esquistossomótica, uma resposta normal do hospedeiro parece ser o suficiente para servir como co-fator da quimioterapia, não havendo portanto indicação para a imunoestimulação artificial nas condições habituais